تحليل مفهوم المعاشرة الزوجية بالمعروف عند محمد حسين الطباطبائي - Muhammad Faisol (Postgraduate Programme of UIN Kiai Haji Achmad Siddiq Jember, 2018)
The main and most important principle that deserves attention in married life is the rule of mu‘āsharah bi al-ma‘rūf (living together in kindness). It is a great principle that guarantees the continuity of intimacy and affection within the family throughout life. It applies equally to both husband and wife. However, we find that scholars have not provided a sufficiently comprehensive explanation of both sides of this principle, despite its importance—especially regarding the woman’s perspective. Therefore, this study examines the views of Muḥammad Ḥusayn al-Ṭabāṭabā’ī, as he is considered more equitable in addressing and researching both sides. This study focuses on and aims to address two main issues, from which several sub-issues emerge: What is the scholarly, religious, and social background of Muḥammad Ḥusayn al-Ṭabāṭabā’ī? What is the concept of mu‘āsharah bi al-ma‘rūf in marital life according to al-Ṭabāṭabā’ī? What are its foundations, structure, essence, and characteristics? The methodology employed in this research is the historical method, as it examines a specific opinion of a historical figure. It also uses a descriptive-analytical approach, in which the researcher describes the structure of al-Ṭabāṭabā’ī’s view, explains the justifications underlying it, analyzes the surrounding context, and interprets these elements. In addition, the researcher traces the intellectual roots of earlier figures who preceded al-Ṭabāṭabā’ī and compares their views with his in order to identify the strengths and weaknesses of his position. The findings of the study are as follows: Al-Ṭabāṭabā’ī grew up in a scholarly family and in an intellectual environment. He studied under prominent teachers in rational sciences, transmitted sciences, and mystical knowledge, until he attained the level of ijtihād. He lived between the two Iranian revolutions and the major Iraqi revolution, which influenced his scholarly and social personality, as reflected in his academic mobility and his revival of rational sciences and Qur’anic exegesis in an effort to rebuild the intellectual independence that the Muslim community had lost. According to al-Ṭabāṭabā’ī, mu‘āsharah bi al-ma‘rūf in marital life is: “a recognized companionship based on the unity of human origin and the diversity of innate dispositions.” His view is distinguished by its detailed treatment, moderation in addressing women’s issues—between Western permissiveness and the restrictions of some scholars—and by its social and philosophical foundations. The weaknesses of his view lie in his failure to provide practical applications, his silence regarding earlier scholars’ opinions, his lack of engagement with transmitted narrations on the subject, and his limited elaboration of this principle in his other works.